Influencing Factors Determination Land Use Change Trend in the Pheryurban Area of Malang City Based On V-Cramer - Annisaa Hamida Imadudinna; Widiyanto Hari Subagyo Widodo; Ibnu Sasongko (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2023)
The rapid urban development of the pheryurban area and the increasing rate of population growth are directly a response to the need for land. The limited land needed to fulfill the development space of a city if it has reached the saturation point has implications for the urban sprawl phenomenon that leads to the pheryurban area. Malang City is the center of the Malang Raya agglomeration area which is one of the prospective metropolitan areas in East Java Province and is part of the Gerbangkertosusila Megapolitan area. The positive externality of the formation of this agglomeration area is the formation of the conurbation phenomenon from the downtown area and the pheryurban area which results in an increase in the area and order of an urban area. The pheryurban phenomenon in Malang City is also strongly influenced by the dominance of the function of the bordering urban core area, for example the area is an industrial area. The development of the pheryurban area in Malang City is also influenced by growth centers both functionally (industry) and geographically (concentration of facilities). The growth center in the form of an industrial area significantly affects the development of the city. This is based on the fulfillment of the need for industrial activities in the form of industrial worker settlements so that the closer the area is to the industrial center, the higher the potential for the area to develop. If viewed from the service center, development will be more directed to areas that are included or reached on the scale of service facilities so that the closer to the center of the facility, the higher the potential for the area to develop. Because of the urgency above, it is very important to do research related to factors that affect land use changes based on v-cramers in the pheryurban area, especially to serve as a basis or justification for future planning so as to be able to get an overview of driving factors and constraint factors in the research area. Knowing these factors is expected to reduce the gap between the existing and the plan so that the planning process in the future will be more optimal and measurable, especially in the realization of the plan.